Islamic Religious Education and Student Academic Achievement and Motivation: A Systematic Review of Pedagogical Strategies and Value Internalization Mechanisms - Yovie Djundjunan; Moh Ali; Saefudin Zuhri (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
Islamic Religious Education (PAI) is mandatory in Indonesia's national curriculum, yet how it shapes academic achievement and motivation remains poorly understood. This systematic review synthesises the pedagogical strategies and mediating factors through which PAI influences these outcomes among Indonesian learners. Following PRISMA 2020 guidelines, we searched Scopus, Web of Science, ERIC, and Garuda for peer-reviewed studies published January 2015 and April 2026; of 312 records, 47 met inclusion criteria after dual independent screening (Cohen's κ = 0.84), with quality appraised using CASP and MMAT and findings synthesised through Braun and Clarke's reflexive thematic analysis. Three mechanisms emerged: intrinsic motivation grounded in religious meaning-making (thalabul 'ilm), non-cognitive competencies cultivated through character-based instruction, and academic identity formed through value internalisation. The review grounds these in a framework linking al-Ghazali's anthropology (nafs, qalb, ruh, 'aql) with Self-Determination Theory and Achievement Goal Theory; the convergence between ikhlas and autonomous motivation is especially productive, as both describe the same inner orientation. Active learning, technology integration, and curricular coherence amplified these mechanisms; teacher quality and institutional leadership moderated their impact on measurable gains. Limitations include restriction to English and Indonesian sources, a ten-year window that underweights foundational work, and the inability to estimate effect sizes. Future meta-analyses, longitudinal studies, and multilingual reviews would address each of these. When pedagogically rigorous and institutionally supported, PAI is a meaningful driver of academic outcomes, not merely a doctrinal subject at the margins of the curriculum, but rather a framework for reform grounded in the Islamic ideal of insan kamil.